Evaluating 3D-printed Bolus Compared to Conventional Bolus Types Used in External Beam Radiation Therapy - McCallum, Stephanie; Maresse, Sharon; Fearns, Peter (Current Medical Imaging, 2021)
Background: When treating superficial tumors with external beam radiation therapy, bolus is often used. Bolus increases surface dose, reduces dose to underlying tissue, and improves dose homogeneity. Introduction: The conventional bolus types used clinically in practice have some disadvantages. The use of Three-Dimensional (3D) printing has the potential to create more effective boluses. CT data is used for dosimetric calculations for these treatments and often to manufacture the customized 3D-printed bolus. Purpose: The aim of this review is to evaluate the published studies that have compared 3D-printed bolus against conventional bolus types. Methods and Results: A systematic search of several databases and a further appraisal for relevance and eligibility resulted in the 14 articles used in this review. The 14 articles were analyzed based on their comparison of 3D-printed bolus and at least one conventional bolus type. Conclusion: The findings of this review indicated that 3D-printed bolus has a number of advantages. Compared to conventional bolus types, 3D-printed bolus was found to have equivalent or improved dosimetric measures, positional accuracy, fit, and uniformity. 3D-printed bolus was also found to benefit workflow efficiency through both time and cost effectiveness. However, factors such as patient comfort and staff perspectives need to be further explored to support the use of 3Dprinted bolus in routine practice.
Keywords: Radiation therapist